AKTIVITAS EKONOMI RUMAH TANGGA TRANSMIGRAN (PENDEKATAN SYSTEM DYNAMICS) - Wahyu Hidayat, M.
Abstract: The purpose of transmigration program is to overcome the asymmetrical spread of population between Java Island and the outside of Java. The program has been oriented toward the settlement pattern based on food base agriculture in both dry field and wet field. Further, the agriculture\'s sector becomes a reference of the policy in transmigration\'s structure, starting from the land allocated to the households in transmigration area until the assistance or consultation activities. Expectantly, the food base agriculture could be as the primary resource of income for the household in transmigration area. This study is an attempt to examine the behavior of economic activity of workforce in transmigration area as a result of the effort to increase their income. This is done through simulation experiments using a system dynamics model of the economic activity of household in transmigration area. Some effort scenarios to increase the household income such as in agriculture sector are considered i.e : increasing the agriculture\'s productivity, extending the agriculture\'s land, and increasing the price of agriculture\'s products. Besides that, the effect of wage increase in non-agriculture sector on the economic activity of workforce was analyzed too. The study shows that the increase of income of the households in transmigration area can be achieved through increasing the price of agriculture\'s products. Besides that, this policy could : - increase the production significantly to 9,000 Kg equally to rice/hectare/year per households; - motivate the households to use all the land that has been allocated to them; and - motivate the households to work fully in agriculture sector. While the wage increase in non-agriculture sector does not increase the income of households in transmigration area as well as their expectation.